2003
DOI: 10.1034/j.1600-0706.2003.11651.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictions of the lake food web theory on pelagic communities of Australian reservoirs

Abstract: Several predictions of the theory developed for pelagic food webs of the Northern Hemisphere were tested on water bodies of Eastern Australia. Eleven reservoirs, representing trophic and latitudinal gradients were sampled for nutrients, phytoplankton, zooplankton and pelagic fish. Two models of regression analysis, which analysed possible interactions between trophic levels were based on different sets of data. In one, each reservoir was represented by only one pair of observations – annual mean or single obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…This was confirmed in later studies, including both observational and experimental data on reservoirs of different productivities during four seasons (Matveev & Matveeva, 1997). A comparative study of pelagic food webs of many reservoirs of south-east Australia, which included subtropical lakes, further confirmed the hypothesis by demonstrating significant negative correlations between zooplankton body size and total phytoplankton biovolume (Matveev, 2003). This suggested that certain configurations of zooplankton structure can regulate phytoplankton biomass.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This was confirmed in later studies, including both observational and experimental data on reservoirs of different productivities during four seasons (Matveev & Matveeva, 1997). A comparative study of pelagic food webs of many reservoirs of south-east Australia, which included subtropical lakes, further confirmed the hypothesis by demonstrating significant negative correlations between zooplankton body size and total phytoplankton biovolume (Matveev, 2003). This suggested that certain configurations of zooplankton structure can regulate phytoplankton biomass.…”
Section: Introductionsupporting
confidence: 57%
“…Small native planktivorous fish, such as gudgeon (Hypseleotris spp. ), can be very abundant in this type of reservoir (Hunt, Matveev, Jones, & Warburton, 2003;Matveev, 2003;Meredith, Matveev, & Mayes, 2003). Gudgeons have been shown to have a stimulatory effect on the abundance of cyanobacteria in mesocosm experiments with lake plankton (Hunt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the northern hemisphere, fish has repeatedly been shown to have a positive effect on phytoplankton abundance and biomass (Christoffersen et al, 1993;Romare et al, 1999;Attayde & Hansson, 2001a, b). The same pattern has been described for the southern hemisphere (Northcote et al, 1990;Quirós, 1990;Jeppesen et al, 2000;Boveri & Quirós, 2002;Matveev, 2003). Although our enclosures nutrient range corresponded to meso-eutrophic lakes, the responses differed from the ones reported for eutrophic systems which according to Jeppesen et al (2003) generally show top-down effects.…”
Section: Discussionsupporting
confidence: 80%
“…Prospects for biomanipulation paradoxically appear theoretically or practically better in Australian reservoirs, in which zooplanktivorous fishes enigmatically appear important (Matveev et al, 2002;Hunt et al, 2003;Matveev, 2003;Sierp et al, 2009), in contrast to South African systems that are otherwise limnologically similar.…”
Section: Discussionmentioning
confidence: 99%